Emerging magic bullet: subcellular organelle-targeted cancer therapy - Yan Yue; Zhang Yimeng; Liu Jianxiong; Chen Binlong; Wang Yiguang (Medical Review)
The therapeutic efficacy of anticancer drugs heavily relies on their concentration and retention at the corresponding target site. Hence, merely increasing the cellular concentration of drugs is insufficient to achieve satisfactory therapeutic outcomes, especially for the drugs that target specific intracellular sites. This necessitates the implementation of more precise targeting strategies to overcome the limitations posed by diffusion distribution and nonspecific interactions within cells. Consequently, subcellular organelle-targeted cancer therapy, characterized by its exceptional precision, have emerged as a promising approach to eradicate cancer cells through the specific disruption of subcellular organelles. Owing to several advantages including minimized dosage and side effect, optimized efficacy, and reversal of multidrug resistance, subcellular organelle-targeted therapies have garnered significant research interest in recent years. In this review, we comprehensively summarize the distribution of drug targets, targeted delivery strategies at various levels, and sophisticated strategies for targeting specific subcellular organelles. Additionally, we highlight the significance of subcellular targeting in cancer therapy and present essential considerations for its clinical translation.